FIELD REVIEW OF THE COMMUNITY OF SOCIAL CUSTOMER RESPONSIBILITY AT PT PERTAMINA, KUPANG AS A FORM OF LECTURER DEDICATION - Pipit Sari Puspitorini (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2020)
KEM is an integral program built on the basis of the collaboration among FlipMAS Indonesia, PT Pertamina, Corporate Social Responsibility (CSR), small Medium Entrepreneur and Partnership Program (SMEPP), and communities with marginal economies using the FlipMAS concept .The method of empowerment were used on 3 principles of FlipMAS Indonesia; Sincerity, Diversity and Territorial with target economically marginalized society with a level of success measured from the indicator of increasing the value of the Human Development Index (HDI) . The success KEM Nunfafo of 8 KEM has changed the society marginalized into the attention of the world internationally, especially the United Nations to talk about the model of empowerment KEM field of agriculture and plantation. Synergy and success in empowering KEM Pertamina flip and sustainability of the program is able to generate an increase in the Human Development Index (HDI) amounted for 44.06% (2015) will approach the HDI districts TTU amounted to 68.94% (2013) with the indicator main is the increase in income per capita .